Smart Metering Cybersecurity—Requirements, Methodology, and Testing - Kohout, David; Lieskovan, Tomáš; Mlýnek, Petr (MDPI, 2023)
This paper addresses the current challenges in cybersecurity of smart metering infrastructure, specifically in relation to the Czech Decree 359/2020 and the DLMS security suite (device language message specification). The authors present a novel testing methodology for verifying cybersecurity requirements, motivated by the need to comply with European directives and legal requirements of the Czech authority. The methodology encompasses testing cybersecurity parameters of smart meters and related infrastructure, as well as evaluating wireless communication technologies in the context of cybersecurity requirements. The article contributes by summarizing the cybersecurity requirements, creating a testing methodology, and evaluating a real smart meter, using the proposed approach. The authors conclude by presenting a methodology that can be replicated and tools that can be used to test smart meters and the related infrastructure. This paper aims to propose a more effective solution and takes a significant step towards improving the cybersecurity of smart metering technologies.

This paper addresses the current challenges in cybersecurity of smart metering infrastructure, specifically in relation to the Czech Decree 359/2020 and the DLMS security suite (device language message specification). The authors present a novel testing methodology for verifying cybersecurity requirements, motivated by the need to comply with European directives and legal requirements of the Czech authority. The methodology encompasses testing cybersecurity parameters of smart meters and related infrastructure, as well as evaluating wireless communication technologies in the context of cybersecurity requirements. The article contributes by summarizing the cybersecurity requirements, creating a testing methodology, and evaluating a real smart meter, using the proposed approach. The authors conclude by presenting a methodology that can be replicated and tools that can be used to test smart meters and the related infrastructure. This paper aims to propose a more effective solution and takes a significant step towards improving the cybersecurity of smart metering technologies.
Smart Metering Cybersecurity—Requirements, Methodology, and Testing
Keywords: methodology; DLMS; smart metering; cybersecurity; AMM; methodology; DLMS; smart metering; cybersecurity; AMM